Mauritius - Fulena, Viraj; Chittoo, Hemant B. (APPS Publications, 2023)
This paper examines the issue of human rights protection for detainees and victims in Mauritius and analyzes whether the country is falling behind in this area. There are significant gaps in human rights protection for detainees and victims in Mauritius, which need to be addressed by the government and civil society. The UK’s human rights mechanisms can play a crucial role in promoting and protecting human rights in Mauritius.